The world colonization made : the racial geography of early American empire - Mills, Brandon (Early American studies., 2020)
"This book is about the colonization movement of the late eighteenth and nineteenth centuries in North America. The colonization movement was a movement and set of ideas to create independent democratic settlements of free African Americans outside the boundaries of the United States: imperialism by another name. Colonizationism was applied also to American Indians; this is how Indian removal began."--